Peran Ustaz dan Ustadzah TPQ Nurul Huda Tlogopragoto dalam Pembinaan Akhlak Santri - Rohmawati, Siti; Mujiono, Slamet (IAINU Kebumen, 2025)
Moral development is an effort or action carried out by a teacher towards students in order to develop morals so that students have noble morals and have commendable habits. This research focuses research on the role of the Ustadz/ustadzah of the Nurul Huda Tlogopragoto Al-Qur'an Education Park in developing the morals of students. The formulation of the problem studied is the role of Ustadz/Ustadzah TPQ Nurul Huda Tlogopragoto in developing the morals of students, and the methods used in developing morals. The research methodology that the author uses is qualitative field research. Data collection in this research uses observation, interviews and documentation methods. The informants in this research were 6 Ustadz/Ustadzah. Based on the research conducted by the author, the author can draw the conclusion that the role of the Ustadz/ustadzah in developing the morals of the students at TPQ Nurul Huda Tlogopragoto has been going well, namely by providing role models, getting the students accustomed to good morals, giving advice, and telling stories/stories to motivate them to have good morals.